The law of EU external relations : cases, materials, and commentary on the EU as an international legal actor - Wouters, Jan, 1964-; Hoffmeister, Frank; Baere, Geert de, 1979-; Ramopoulos, Thomas (New York, NY : Oxford University Press, 2021)
This compilation of materials, cases, and commentary on EU external relations law is both a valuable teaching tool for (post-)graduate courses and seminars on the foreign relations of the European Union, as well as an indispensable first initiation in the legal foundations of the external action of the Union for diplomats, civil servants, attorneys, and other practitioners. Apart from making accessible key primary materials such as EU Treaty provisions; judgments and opinions of the Court of Justice; legislation; agreements; and more obscure documents revealing the law in practice, the book includes concise, expert legal analysis of these materials. The third edition of the book incorporates more than ten years of fascinating dynamics since the entry into force of the Lisbon Treaty.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 8, 2021).
Keywords: European Union; European Union countries -- Foreign relations -- Law and legislation